Teachers' perceived societal appreciation: PISA outcomes predict whether teachers feel valued in society. (2021) - Spruyt, Bram; Van Droogenbroeck, Filip; Van Den Borre, Laura; Emery, Laura; Keppens, Gil; Siongers, Jessy
Highlights: Feelings of PSA tap into feelings of collective social self-esteem among teachers. Systematic Individual- and School level differences in PSA are modest. Large between country differences in PSA were found. A within-country trend in PISA scores predicts a trend in levels of PSA. Abstract: Typical of the teaching profession is the multitude of actors that comment on and evaluate teachers' work. Previous studies indicate that teachers feel that their work is relatively underappreciated in society. Little is known about the dynamics that explain apparent variation in this feeling. Based on data from 66, 593 teachers in 25 countries we study variation of Perceived Societal Appreciation (PSA). We find robust evidence that a change within countries in PISA scores predicts a within country trend in levels of PSA. In the conclusion we critically engage with contemporary OECD policies by arguing that inducing a crisis mentality about educational quality risks accomplishing the exact opposite than what one aims for.